Diagnostic Value of Axillary Ultrasound, MRI, and 18F-FDG-PET/ CT in Determining Axillary Lymph Node Status in Breast Cancer Patients - Ayşegül Aktaş; Meryem Günay Gürleyik; Sibel Aydın Aksu; Fugen Aker; Serkan Güngör (European Journal of Breast Health, 2022)

(untitled)
Objective:Knowing axillary lymph node (ALN) status before surgery affects decisions about treatment modalities. Therefore, reliable, noninvasive diagnostic methods are important for determining ALN metastases. We aimed to accurately evaluate the patient’s ALN status with noninvasive imaging modalities while making treatment decisions.Materials and Methods:Patients who received the axillary ultrasound (AUS), magnetic resonance imaging (MRI), or 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG-PET/CT) imaging modalities and whose ALNs were confirmed histopathologically by fine needle aspiration cytology (FNAC), sentinel lymph node biopsy (SLNB), or ALN dissection (ALND) were included in the study.Results:The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of AUS for the detection of ALN metastases were 83%, 62%, 59.2%, 54.8%, and 79.1%, respectively. For MRI they were 86.1%, 75%, 68.5%, 51.6%, and 85.3%, respectively, and for 18F-FDG-PET/CT they were 78%, 53%, 56.2%, 51.4%, and 72.5%, respectively. ALNs were found to be metastatic in all patients who were reported positive in all three imaging modalities. ALN metastases were detected in 19 of 132 patients (false negativity, 14.3%) in whom AUS, MRI, and 18F-FDG-PET/ CT images were all reported as negative.Conclusion:In our study, we found that the diagnostic performance of MRI was slightly better than AUS and 18F-FDG-PET/CT. When we used imaging modalities together, our accuracy rate was better than when we used them alone. For accurate evaluation of axillary lymph nodes, imaging modalities should be complementary rather than competitive.